To assess the viability of a new service concept and to develop a comprehensive business plan for an energy management consultancy (EMREG) - Ansong, Lilian; Singh, Virender; Kuyucuoglu, Orcun (2012)
The purpose of this study was to establish the feasibility and viability of a proposed new, high profile, specialist B2B service called Part Time Energy Management. Based on this, a business plan was to be developed in order to identify the most appropriate strategies for EMREG to pursue in delivering this service.